Pharmacokinetics and Biological Activity of Cucurbitacins - Eugenia Elisa Delgado-Tiburcio; Jorge Cadena-Iñiguez; Edelmiro Santiago-Osorio; Lucero del Mar Ruiz-Posadas; Israel Castillo-Juárez; Itzen Aguiñiga-Sánchez; Marcos Soto-Hernández (MDPI AG, 2022)
Cucurbitacins are a class of secondary metabolites initially isolated from the Cucurbitaceae family. They are important for their analgesic, anti-inflammatory, antimicrobial, antiviral, and anticancer biological actions. This review addresses pharmacokinetic parameters recently reported, including absorption, metabolism, distribution, and elimination phases of cucurbitacins. It includes recent studies of the molecular mechanisms of the biological activity of the most studied cucurbitacins and some derivatives, especially their anticancer capacity, to propose the integration of the pharmacokinetic profiles of cucurbitacins and the possibilities of their use. The main botanical genera and species of American origin that have been studied, and others whose chemo taxonomy makes them essential sources for the extraction of these metabolites, are summarized.